The evolution of a new class of CO2 absorbents: Aromatic amines. (April 2019) - Puxty, Graeme; Conway, Will; Yang, Qi; Bennett, Robert; Fernandes, Debra; Pearson, Pauline; Maher, Dan; Feron, Paul
Highlights: Overview of why amines containing aromatic functionality should be considered as CO2 absorbents. A combination of calculation and pilot plant results highlight the performance of aromatic amines. Overall, aromatic amines (as defined here) combine capture performance and stability along with low toxicity and biodegradability. Abstract: Aqueous amines are the most common and technically mature class of chemical absorbents used for CO2 separation applications. They have been developed over decades and have the capability to be tuned to operate under a range of gas compositions and achieve very high levels of CO2 removal. Previously non-cyclic and some cyclic aliphatic amine molecules have been used. Aromatic amines have not received significant consideration. In this work it is argued that the structural rigidity and stability that aromaticity affords gives these amines a unique set of properties in terms of absorption performance, stability and biodegradability that means they should be considered as a promising class of amine for CO2 absorption applications.